2020
DOI: 10.1111/ijfs.14755
|View full text |Cite
|
Sign up to set email alerts
|

Hempseed as a nutritious and healthy human food or animal feed source: a review

Abstract: Summary Hempseed products are projected to receive great potentials due to the rapid growth in the US market. Industrial hemp has been an important crop for food, fibre and medicine applications. Hempseed products can be used as nutraceutical supplements and functional foods for human and can be applied for animal feed. This review provides a comprehensive summary of nutritional quality and health benefits of hempseed which is attributed to high levels of essential fatty acids and other PUFAs in the oil, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 84 publications
3
31
0
1
Order By: Relevance
“…Hemp inflorescences biosynthesise quite unique health beneficial phytocannabinoids, while hemp seeds are an excellent source of high-value oil, proteins, and valuable micronutrients [6], including health beneficial bioactive compounds [7,8]. For instance, Pihlanto et al [9] reported 5.88-10.63 mg total phenolic content (expressed in mg of gallic acid equivalents) per gram of dry defatted hemp seed flour, which was also confirmed by Rea et al [10].…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Hemp inflorescences biosynthesise quite unique health beneficial phytocannabinoids, while hemp seeds are an excellent source of high-value oil, proteins, and valuable micronutrients [6], including health beneficial bioactive compounds [7,8]. For instance, Pihlanto et al [9] reported 5.88-10.63 mg total phenolic content (expressed in mg of gallic acid equivalents) per gram of dry defatted hemp seed flour, which was also confirmed by Rea et al [10].…”
Section: Introductionmentioning
confidence: 73%
“…The same tendency may be observed in the samples with RH, while in the case using RH with SG, the effect of hemp seed press-cake may be explained by its water-binding capacity. Raikos et al [31], Xu et al [6], and Zając et al [32] reported that hemp protein or hemp flour with high protein content improves the products' water holding capacity. Therefore, the lower grilling losses with hemp additives may be useful for producers to help retain the moisture inside the product.…”
Section: Proximate Composition and Grilling Losses Of Pork Burger Pattiesmentioning
confidence: 99%
“…Industrial hemp ( C. sativa L. supsp. sativa ), generally refer to hemp, has <0.3% of tetrahydrocannabinol (THC), a higher plant height, and the main parts used are seeds and fiber ( 2 ). Owing to its low THC content, industrial hemp is unable to stimulate human nerves, therefore, has a potential to be grown as a safe crop ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Only in recent times the discovery of hemp seeds' high nutritional value led to a revaluation of this source for human consumption. Literature regarding the investigation of hemp seeds' composition has increased, making them an emerging source for value-added functional food ingredients and nutraceuticals [5,6]. Hemp seeds are consumed shelled in salad dressings, and in the production of snack bars, or they can be cold pressed to obtain edible hemp seed oil, and the residual cake is grinded to have a fiber-rich flour used in processed food (such as bread, biscuits, and pasta).…”
Section: Introductionmentioning
confidence: 99%